2023
DOI: 10.1039/d3cp02844e
|View full text |Cite
|
Sign up to set email alerts
|

Symmetry-breaking-induced ferroelectric HfSnX3 monolayers and their tunable Janus structures: promising candidates for photocatalysts and nanoelectronics

Yu Zhang,
Yanqing Shen,
Jiajia Liu
et al.

Abstract: HfSnX3 and Janus HGSS monolayers: materials with great application prospects in ferroelectric adjustable energy conversion and nano electronic devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…Thus, the electron (hole) transfer from intermediate ZnSnSe 2 to upper (lower) graphene is induced, which gives rise to higher carrier density and thereby elevated conductivity of the graphene. [67] Taken together, the intrinsic electric fields of Janus ZnXY 2 are expected to promote a more sensitive photo-current response with proper substrates, [68] showing promise as ideal photocatalytic materials for economical and efficient solar energy utilization.…”
Section: Practical Photocatalytic Applicationmentioning
confidence: 99%
“…Thus, the electron (hole) transfer from intermediate ZnSnSe 2 to upper (lower) graphene is induced, which gives rise to higher carrier density and thereby elevated conductivity of the graphene. [67] Taken together, the intrinsic electric fields of Janus ZnXY 2 are expected to promote a more sensitive photo-current response with proper substrates, [68] showing promise as ideal photocatalytic materials for economical and efficient solar energy utilization.…”
Section: Practical Photocatalytic Applicationmentioning
confidence: 99%
“…It is well-known that symmetry breaking in 2D materials holds significant potential to trigger emerging phenomena. The breaking of symmetry typically induces an intrinsic electric field within the monolayer, resulting in various properties such as ultrahigh carrier mobilities, piezoelectricity, the Rashba effect, ferroelectricity, catalytic properties, and high hydrogen evolution reaction activity . Consequently, exploring symmetry breaking in 2D materials not only sheds light on fundamental physics principles but also holds promise for technological advancements in various fields from electronics to catalysis.…”
Section: Introductionmentioning
confidence: 99%
“…11 In materials science, Janus indicates materials with different properties on two opposing sides or faces. 12,13 Recently, Janus 2D materials have emerged as a new interesting class of materials. 14−18 Both experiments and materials models have confirmed that these materials show novel peculiar properties compared to their 2D parent sheets, such as strong Rashba effect and out-of-plane spontaneous polarization.…”
Section: Introductionmentioning
confidence: 99%
“…Janus, the God of transitions and dualities in Roman mythology, has two faces and holds the key to the liminal space of the past and future so that it can simultaneously see both the past and the future . In materials science, Janus indicates materials with different properties on two opposing sides or faces. , Recently, Janus 2D materials have emerged as a new interesting class of materials. Both experiments and materials models have confirmed that these materials show novel peculiar properties compared to their 2D parent sheets, such as strong Rashba effect and out-of-plane spontaneous polarization. In previous studies, it was found that the lattice mismatch between the inner and outer atomic layers of 2D Janus structures can spontaneously drive the 2D sheet to wrap into a 1D structure . Recently, using Density Functional Theory (DFT), Bölle and coworkers have explored the class of Janus transition metal dichalcogenide and halide nanotubes, discovering a handful of compositions that spontaneously wrap, forming tubes with a diameter smaller than 10 nm.…”
Section: Introductionmentioning
confidence: 99%